A Comprehensive Review of Blockchain-Enabled Open-Source Tools for Managing Electronic Health Records (EHR) in Hospitals - Shaik, Zahid Hussain; poonia, Kelapati (Journal of Trends in Computer Science and Smart Technology, 2025)
Currently, blockchain technology is becoming the potential innovation within a healthcare sector. This systematic review studies the literature regarding blockchain and blockchain adoption in healthcare with an emphasis on hospital Electronic Health Record (EHR) management. This study presents two objectives - identifying gaps in the current research pipeline and suggesting future research recommendations. The first task as part of the study is to analyze the opportunities and challenges associated with applying blockchain technology in the healthcare sector. To accomplish these objectives and assess the position of blockchain technology in the field, a systematic literature review was performed using credible scientific databases and conference papers. Some of the terms from the study glossary that were used as literature search terms included "Blockchain," "implementation," Of the relevant articles originally selected, 32 articles were deemed relevant of which 26 articles contained the elements necessary to conduct factor analysis. The authors of the selected articles presented the analysis of a framework for EHR management in 22 of these articles, that included classification, implementation forms and research gaps. This review shows that there are potential advantages to using blockchain technology in healthcare notable benefits include better data security, improved interoperability, and enhanced patient privacy. A transaction in Blockchain (Ethereum) cost 8 US cents. The evaluation of performance included a designed assessment and metrics that includes, 18.29 s execution time, throughput with 100 to 500 users for a period of 10 to 35, and a latency of 14ms. Among the very important contributions of this review was identifying existing research gaps and providing an exploratory analysis to inform future research efforts. By identifying these gaps, researchers can continue to investigate innovative blockchain applications in healthcare and apply its implementation across a range of clinical scenarios. As part of using blockchain technology to implement EHR management; this systematic review adds to existing scholarship on implementing blockchain technology in healthcare.